The leverage and company size impact on delay in the audit - Ramdani, Doni; Prayitno, Yogo Heru (Goodwood Publishing, 2023)
Purpose: The goal of this study is to investigate the impact of leverage and company size on the delay in auditing of manufacturing companies listed on the IDX (2016-2018). Research methodology: Descriptive and vericative methods were used for the study design. The purposive judgement sampling method was used for sample determination in the present study. The program used was SPSS Version 20.00. Results: The findings show that simultaneously variable leverage and company size affect audit delays. Limitations: This study only uses data from the IDX for 2016-2018 which allows data not to be obtained in detail, and the sample in this study only uses manufacturing companies that use rupiah currency. Contribution: Author, Idx, and Public.